Income Elasticities Without Parameters - Per Hjertstrand (Research Institute of Industrial Economics (IFN), 2020)
This paper proposes a simple non-parametric framework to calculate income elasticities from a data set of observed prices and consumed quantities without having to estimate any parameters. The framework can be applied when the price-quantity data satisfies a revealed preference axiom called the strong version of the strong axiom of revealed preference (SSARP). The framework is used to calculate income elasticities for food and non-alcoholic drinks from a rich panel of household expenditures. For this category, it is found that households are rather homogeneous in their demand responses.
Keywords: D11; D12; 330; Income elasticity; Non-parametric; Revealed preference; SSARP